An Equivalent Circuit Model for Lithium-sulfur Batteries. (May 2017) - Jiang, Jiuchun; Liang, Yan; Ju, Qun; Zhang, Linjing; Zhang, Weige; Zhang, Caiping
Abstract: Battery Management System (BMS) plays a very important role in monitoring the state of batteries in electric vehicles (EVs) or other energy storage systems. However, the reliability of the state monitoring largely depends on the accuracy of the established model. Recently, lithium-sulfur battery has attracted much attention due to its high energy density (2600Wh/kg of theoretical specific energy). It is very important to establish an accurate and appropriate model for its practical application. In this paper, the first-order RC equivalent circuit model is introduced, which is established based on the charging and discharging characteristics of lithium-sulfur batteries and parameter identification test. The simulation results show that the equivalent circuit model can fit the V-I characteristics of lithium-sulfur batteries well to a certain extent, especially for the low current rate.